The split-off terahertz radiating dipoles on thermally reduced α-V2O5 (001) surface. Issue 41 (20th October 2020) - Wang, Q. J.; Wang, H.; Zhou, Z. H.; Zuo, J.; Zhang, C. L.
Abstract : The formation of vanadyl oxygen defects leads to a transient charge distribution that forms terahertz radiating dipoles on the V2 O5 (001) surface. Abstract : The trapped electron states on a pliable lattice have different localization and physical chemistry characteristics. Here, terahertz time-domain measurements suggest that the formation of vanadyl oxygen defect, in the presence of the surface potential traps and mobile charge carriers, leads to a transient charge distribution that forms terahertz radiating dipoles in V2 O5 . The emergence of radiating dipoles is evidenced by terahertz responses with a two-valley feature of the thermally reduced α-V2 O5 (001) thin films in the temperature range of 300–700 K. The two photoconductance valleys on a several millielectron volts interval are related to two emergent split-off traps, which originate from the VO6 octahedra distortion upon the vanadyl oxygen desorption on the surface. The pliable surface lattices plays a decisive role. So long as the α-V2 O5 (001) thin films are covered by a 30 nm-thick Al2 O3 capping layer, the distinct two-valley feature disappears completely in the full temperature range. The terahertz radiating dipoles with a fine energy structure is potentially a new measure for charge dynamics on the α-V2 O5 (001) surface.